Examining the Effectiveness of Instagram Vlogs on Speaking Proficiency of Aerospace Engineering Students - Maria Asumpta Deny Kusumaningrum; Dewanti Ratna Pertiwi (English Education Journal, 2022)
This research aims to show how Instagram vlogs may be used in the classroom as a technological tool. This research mentions the usage of Instagram vlogs to help students improve their speaking skills. The challenges that aerospace engineering students had throughout the speech were described using a case study. Internal factors including language proficiency, motivation, and anxiety were employed to investigate these anxieties. This research involved 49 students. SPSS statistics were used to examine the first instrument (pre-test and post-test) as well as the second instrument (questionnaire). Their speaking abilities had improved, according to the data. The students struggled with correct grammar use, vocabulary choices, and pronunciation as they progressed with their vlogs. When they were vlogging, they were also nervous. On the other hand, they were motivated. This study was reinforced by some of the authors' practices using Instagram vlogs as well as relevant research findings and literature. The research findings revealed that using Instagram vlogs contributed to EFL students improving their speaking skills by increasing fluency, confidence, motivation, and learning new vocabulary.